Insights into the hyperglycosylation of human chorionic gonadotropin revealed by glycomics analysis - Ibeto, Linda; Antonopoulos, Aristotelis; Grassi, Paola; Pang, Poh-Choo; Panico, Maria; Bobdiwala, Shabnam; Al-Memar, Maya; Davis, Paul; Davis, Mark; Norman Taylor, Julian; Almeida, Paula; Johnson, Mark R.; et al. (PloS one, 2020)
Human chorionic gonadotropin (hCG) is a glycoprotein hormone that is essential for the maintenance of pregnancy. Glycosylation of hCG is known to be essential for its biological activity. "Hyperglycosylated" variants secreted during early pregnancy have been proposed to be involved in initial implantation of the embryo and as a potential diagnostic marker for gestational diseases. However, what constitutes "hyperglycosylation" is not yet fully understood. In this study, we perform comparative N-glycomic analysis of hCG expressed in the same individuals during early and late pregnancy to help provide new insights into hCG function, reveal new targets for diagnostics and clarify the identity of hyperglycosylated hCG. hCG was isolated in urine collected from women at 7 weeks and 20 weeks' gestation. hCG was also isolated in urine from women diagnosed with gestational trophoblastic disease (GTD). We used glycomics methodologies including matrix assisted laser desorption/ionisation-time of flight (MALDI-TOF) mass spectrometry (MS) and MS/MS methods to characterise the N-glycans associated with hCG purified from the individual samples. The structures identified on the early pregnancy (EP-hCG) and late pregnancy (LP-hCG) samples corresponded to mono-, bi-, tri-, and tetra-antennary N-glycans. A novel finding was the presence of substantial amounts of bisected type N-glycans in pregnancy hCG samples, which were present at much lower levels in GTD samples. A second novel observation was the presence of abundant LewisX antigens on the bisected N-glycans. GTD-hCG had fewer glycoforms which constituted a subset of those found in normal pregnancy. When compared to EP-hCG, GTD-hCG samples had decreased signals for tri- and tetra-antennary N-glycans. In terms of terminal epitopes, GTD-hCG had increased signals for sialylated structures, while LewisX antigens were of very minor abundance. hCG carries the same N-glycans throughout pregnancy but in different proportions. The N-glycan repertoire is more diverse than previously reported. Bisected and LewisX structures are potential targets for diagnostics. hCG isolated from pregnancy urine inhibits NK cell cytotoxicity in vitro at nanomolar levels and bisected type glycans have previously been implicated in the suppression of NK cell cytotoxicity, suggesting that hCG-related bisected type N-glycans may directly suppress NK cell cytotoxicity.